The Phyto-chemical and Lipid Oxidation Quantification of the Aqueous, N-hexane and Petroleum Ether Extracts of Fermented Pawpaw (Carica papaya L.) Seed - M.O, Adesola; E.A, Akande; H.A, Agboola (Current Perspectives in Agriculture and Food Science Vol. 9, 2024)
This research was aimed at evaluating the effect of extracting solvents on the yield, phytochemical compounds and selected chemical properties of fermented pawpaw (Carica papaya) seed. Fruit seeds contain several phytochemical compounds that have been reported to show antiviral, anti-allergic, anti-inflammatory, antitumor and antioxidant activities. Due to the varied chemical properties of these seeds, different solvents are used in the extraction. However, care must be taken in the choice of solvent used for the extraction because it will determine the yield and the quality of the extract in terms of the phytochemical content. Extracts from fermented T-solo variety of pawpaw seeds were obtained using petroleum ether, n-hexane and hot aqueous solvents using standard method. Analysis was carried out to determine some qualitative and quantitative phyto-chemical and some selected chemical compositions (Peroxide Value PV and Thiobarbituric Acid Value TBA. Extracts’ yield was 26.00, 23.30 and 19.51% for petroleum ether, n-hexane and hot aqueous solvent, respectively. The result of the quantitative analysis shows that all the phytochemicals were more abundant in petroleum ether extract. The PV and TBA of n-hexane, petroleum ether and hot water extract were 5.32, 4.52, 0.00 meq/kg and 0.87, 0.16, 0.09 \(μ\)g/kg respectively. It is evident that petroleum ether extract contains more phytochemical compounds than the other extracts so it is likely to have more antioxidant activities since antioxidant activities are associated with phytochemicals. The PV and TBA obtained for petroleum ether extract were relatively low and this implied that the extract will undergo little or no autoxidation or oxidative deterioration when used. The peroxide value and thiobarbituric acid value obtained for petroleum ether extract were relatively low and this implied that the extract would undergo little or no autoxidation or oxidative deterioration when used. This indicates that the extract can be a good preservative.